STUDI KASUS SISWA TERLAMBAT MENGIKUTI PELAJARAN SOSIOLOGI KELAS XI SMAN 9 PONTIANAK TAHUN 2017 - Fazry, Saiful; Asrori, M; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study entitled case study about students often late to follow the sociology class XI SMA Negeri 9 Pontianak. common problem in this research is how effort to help student often late to follow Sosiology class XI SMA Negeri 9 Pontianak. While the purpose in this study to find the cause, aid efforts and results obtained after being given guidance on students often late to follow the lessons of sociology. The approach used is qualitative approach by using descriptive method and form of research is case study research. two case subjects in this study, for the first case subject to using alternative assistance model of RET counseling and form of treatment using directive and didactic techniques, so that irrational mindset becomes a rational mindset. While the second assistance is to use assertive therapy and systematic desentisisasi in Behavioral Counseling Models so that the behavior of case subjects to be good.Keywords: Case Study, Student, Late to Coming to Class.